(untitled) (Nigerian Journal of Physiological Sciences, 2024)
Rauvolfia vomitoria is a medicinal plant that has been implicated by various scientific studies as possessing strong anti-diabetic action; however, the mechanism of action is lacking. Hence this study investigated the anti-diabetic mechanisms of action of Rauvolfia vomitoria through in vitro and in vivo studies. In the in vitro study, the α-amylase and α-glucosidase inhibitory activities of hydromethanolic Rauvolfia vomitoria leaf extract were investigated in comparison with acarbose; while in the in vivo, the effect of the extract on plasma insulin levels of normal and streptozotocin-induced diabetic wistar rats were investigated in comparison with glyburide. Results from the in vitro study showed the percentage inhibition of α-amylase by the extract (100 mg/ml) to be 62.28 (4.73) with an IC50 values of 74.35 mg/ml, while acarbose had a percentage inhibition and IC50 values of 72.81 (2.52) and 66.05μg/ml, respectively. The percentage inhibition of α-glucosidase by the extract (100 mg/ml) was 79.63 (4.09) and an IC50 values of 58.85 mg/ml, while acarbose had a percentage inhibition and IC50 values of 82.11 (1.84) and 56.79μg/ml, respectively. From the in vivo study, the result showed that the extract caused a dose and treatment-duration dependent significant (P<0.05) increase in the plasma insulin levels of streptozotocin-induced diabetic rats in a manner comparable to glyburide. From the results of these investigations, it is therefore concluded that Rauvolfia vomitoria leaf effect its anti-diabetic actions via two separate mechanisms; the plasma insulin increasing mechanism and the α-amylase and α-glucosidase inhibitory mechanism. Keywords: Rauvolfia vomitoria leaf extract, α-amylase, α-glucosidase, plasma insulin, acarbose, glyburide.